Penilaian Kualitas Hidup Pasien Hemodialisis Rutin dengan Anemia di Yogyakarta - Candra Eka Puspitasari; Tri Murti Andayani; Fredie Irijanto (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Anemia is often experienced by hemodialysis patients and can have an impact on the quality of life. This study aims to determine the effect of hemoglobin (Hb), hematocrit (Ht), and the characteristics and sociodemographic of the subjects on quality of life. The method used in this study was cross sectional and consecutive sampling technique. The data is retrieved by interviews which then analyzed using dummy multiple regression. Inclusion criteria included routine hemodialysis patients and did not receive blood transfusions. The validity and reliability test of the KDQoL-SF36 questionnaire showed reliable results. The results of the study on 112 subjects obtained an increase in Hb levels positively correlated with an increase in the KDQoL-SF36 score but not for an increase in Ht levels. Increased KDQoL-SF36 score illustrates the better quality of life of patients. Characteristics and sociodemography that influence quality of life include comorbid dummy hypertension-diabetes and work status. The condition of anemia can worsen the quality of life for hemodialysis patients.